New Map of the Whole World with the Trade winds: According to ye latest and most Exact Observations By H. Moll Geographer - Moll, Herman, d. 1732 (Bowles, Thomas d. 1767 Bowles, John 1701-1779, 1729)
18th century Copper engraving. Printed at top: "A New Map of the Whole World with the Trade winds According to ye latest and most Exact Observations By H. Moll Geographer." Printed in upper left corner: "In this Maps is inserted A Few of ye General & Coasting Trade-winds, Monsoons or ye Shifting Trade-winds. Note that ye Arrows among ye Lines shew ye Course of those General & Coasting winds and ye arrows in ye void Spaces shew ye course of ye Shifting Trade-winds and ye Abbreviation Sept etc. Shew ye Times of ye Year when such Winds Blow." Printed in upper right corner: "The Signs of the Zodiack. The First 5 are Northern, the other Southern Signs." [Map lists names of each Zodiac sign with accompanying symbol and month.] Printed beneath the border: "Printed for Thos. Bowles Print and MapSeller next ye Chapter House in St. Pauls Churchyard, and John Bowles Print and Map Seller at the Black Horse in Cornhill London." Printed in upper left-hand corner outside of map border: "1." Inset in center of upper portion of the map: "North Pole." Of note, California is shown as an island off the coast of North America. Siberia is referred to as "Parts Unknown" and Australia is called "New Holland." Depictions of trade winds are shown with shading and arrows. A line marked as "The Zodiack" curves around the equator containing the symbols for the Zodiac signs listed in the Zodiac key. Beneath the two hemispheres, detailed depictions of people surrounding a goddess distributing gifts are shown with armed soldiers at the edge of the crowd and natives armed with bows and arrows at the far sides of the illustrations. London meridian Scale: c.a. 1:200,000,0000 This map was originally created by Dutch cartographer, engraver and bookseller, Herman Moll (?-1732). Moll first came to England in 1678. He worked as an engraver for Moses Pitt, Greenville Collins, John Adair, and Seller and Price. Some of his work includes "America and Europe" for Moore's "Geography" (1681), six charts for Collins in 1689, "A System of Geography" (1701), "Globe" (1703), "Atlas Minor" (1727, 1729), and "World Described" (1727) (Tooley, 444). He was a major proponent of the concept that California was an island even after exploration information from Jesuit Father Kino revealed that California was a peninsula in 1705. This map, first published in Moll's "Atlas Minor" in 1729, for instance, depicts California as an island. This map was later published in Salmon's "Modern history" (1736), Moll's second edition of "Atlas Minor" (1732) and the third edition (1736) (Wagner, 330). Many of Moll's other maps were used by the British to contest France's claims on certain land borders following the War of Spanish Succession (1702-1713) (Portinaro and Knirsch, 317). (Wagner, 330). Source(s): Portinaro, Pierluigi and Franco Knirsch. "The Cartography of North America 1500-1800." New York: Facts on File, Inc., 1987. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979. Wagner, Henry R. "The Cartography of the Northwest Coast of America to the year 1800 Volume 2." Berkeley: University of California Press, 1937.